Knowledge of solid waste management through composting: A comparative study of rural communities in Malaysia and Indonesia - Anwar, A; Amaranti, R; Satori, M; Salleh, N A (IOP Publishing Ltd, 2020)
Along with increasing human activity, the waste generated from these activities more and more. Waste at this time has become one of the causes of disasters in the world. One type of waste produced is organic waste. Organic waste is one of the solid wastes produced from domestic waste. Research is conducted to understand how people carry out organic waste processing into compost, to improve the quality of life, especially in economic terms. In addition, it can be identified factors and obstacles that affect the community when processing organic waste into compost. Primary data collection is done through interviews and field observations in selected rural communities. While secondary data collection is done by literature study. This research was conducted by taking samples in rural communities in Indonesia and Malaysia. The results obtained show a comparison of the patterns of success of rural communities in Indonesia and Malaysia in processing waste into compost.